Selected physiological effects of a Garcinia gummi-gutta extract in rats fed with different hypercaloric diets - Guillén-Enríquez, Carolina (2018)
Garcinia gummi-gutta (GGG) rind extract is effective for reducing appetite, body weight and adiposity of obese rodents fed high-fat (HF), high-sugar (HS) or high fat/sugar (HFS)-based diets, but these effects have not been simultaneously evaluated. Thirty obese (~425 g) male Wistar rats were fed for eleven weeks with six hypercaloric diets (4.1 kcal/g; five rats/diet) non-supplemented (HF, HS, HFS), or supplemented (HF+, HS+, HFS+) with GGG extract (5.9%), while rats from the control group (375 g) were fed a normocaloric diet (3.5 kcal/g). Body weight, dietary intake, body fat distribution, and histological and biochemical parameters were recorded. Compared to control rats, non-supplemented and supplemented groups consumed significantly less food (14.3% and 24.6% (−4.3 g/day), respectively) (p < 0.05). Weight loss was greater in the HF+ group (35–52 g), which consumed 1.9 times less food than the HS+ or HFS+ fed groups. The HF and HFS groups showed 40% less plasma triacylglycerides and lower glucose levels compared to the HF+. GGG-supplemented diets were associated with lower ketonuria. The HF+ diet was associated with the best anti-adiposity effect (as measured with the dual X-ray absorptiometry (DXA) and Soxhlet methods). The severity of hepatocyte lipidosis was HF > control > HF+, and no signs of toxicity in the testes were observed. The results indicate that GGG is more effective when co-administered with HF diets in obese rats